A Triple-Electrode Based Dual-Biosensor System Utilizing Track-Etched Microporous Membrane Electrodes for the Simultaneous Determination of l-Lactate and d-Glucose - Mizuguchi, Hitoshi; Sasaki, Keiko; Ichinose, Hirokazu; Seino, Shota; Sakurai, Jun; Iiyama, Masamitsu; Kijima, Tatsuro; Tachibana, Kazuhiro; Nishina, Tatsuo; Takayanagi, Toshio; Shida, Junichi (Bulletin of the Chemical Society of Japan, 2017)
A new triple-electrode system was developed for the simultaneous determination of l-lactate and d-glucose by using track-etched microporous membrane electrodes, which enabled efficient electrolysis as electroactive substances passed through the electrode. The proposed biosensor was fabricated by alternate stacking of the electrodes and immobilized enzyme reactors along the flow direction of the sample solution. When the sample solution containing l-lactate and d-glucose flowed into the proposed biosensor, hydrogen peroxide was produced by each enzymatic reaction and detected individually by anodization at each detector-electrode positioned downstream of each enzyme reactor. The interfering substances, such as l-ascorbic acid and uric acid, were electrolyzed completely at the pre-reactor electrode that was positioned upstream of the enzyme reactors. As a result, the simultaneous detection of l-lactate and d-glucose was achieved with no other catalytic material such as peroxidase or an electron mediator in the presence of the interferents at physiological concentrations in human blood.